Implementasi Hukum Waris Islam dalam Masyarakat Pedesaan: Studi Kualitatif di Desa Balung, Kabupaten Kampar - Winario, Mohd (EL-EMIR Institute, 2025)
This study aims to understand how Islamic inheritance law is implemented in inheritance practices within the community of Balung Village, Kampar Regency. The focus of the research is to explore the community's understanding, attitudes, and behaviors toward the provisions of Islamic inheritance law, as well as the factors influencing its application. This study uses a qualitative approach with a case study method. Data were collected through in-depth interviews, participatory observation, and documentation. The primary informants consisted of religious leaders, heirs, and village officials. The findings indicate that although most of the people in Balung Village are aware of the basic principles of Islamic inheritance law, its implementation does not fully adhere to Sharia provisions. The influencing factors include local traditions, family agreements, limited legal understanding, and the roles of customary and religious leaders in the inheritance distribution process. This study concludes that an educational and collaborative approach involving religious leaders, village authorities, and the community is necessary to encourage a more consistent and fair application of Islamic inheritance law.